2009
DOI: 10.1016/j.bone.2009.07.078
|View full text |Cite
|
Sign up to set email alerts
|

Beam hardening artifacts in micro-computed tomography scanning can be reduced by X-ray beam filtration and the resulting images can be used to accurately measure BMD

Abstract: Bone mineral density (BMD) measurements are critical in many research studies investigating skeletal integrity. For preclinical research, micro-computed tomography (μCT) has become an essential tool in these studies. However, the ability to measure the BMD, directly from μCT images can be biased by artifacts such as beam hardening, in the image. This three-part study was designed to understand how the image acquisition process can affect the resulting BMD measurements and to verify that the BMD measurements ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
133
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(139 citation statements)
references
References 64 publications
1
133
0
5
Order By: Relevance
“…Anesthetized mice were injected intravenously with 100 mL phosphate-buffered saline (PBS) containing 2 nmol of dissolved OsteoSense750EX (PerkinElmer, Waltham, MA, USA), a fluorescently conjugated pamidronate derivative, (21) and imaged 2,4,6,8,10,15,20, and 30 minutes after injection using the NightOwl planar imaging system (Berthold Technologies, Bad Wildbad, Germany) to qualitatively determine kinetic distribution. A phantom was placed over the mouse bladder to help position the limbs and prevent obscuring of the limb signal from the urinary pool of bisphosphonate.…”
Section: Bisphosphonate Binding Kineticsmentioning
confidence: 99%
“…Anesthetized mice were injected intravenously with 100 mL phosphate-buffered saline (PBS) containing 2 nmol of dissolved OsteoSense750EX (PerkinElmer, Waltham, MA, USA), a fluorescently conjugated pamidronate derivative, (21) and imaged 2,4,6,8,10,15,20, and 30 minutes after injection using the NightOwl planar imaging system (Berthold Technologies, Bad Wildbad, Germany) to qualitatively determine kinetic distribution. A phantom was placed over the mouse bladder to help position the limbs and prevent obscuring of the limb signal from the urinary pool of bisphosphonate.…”
Section: Bisphosphonate Binding Kineticsmentioning
confidence: 99%
“…Indeed errors of up to 30% can be incurred due to beam hardening in estimating bone densities for 10 mm samples at 80 kV. 246 Consequently, it is very important for quantitative densitometry to make sure that the grey level fluctuation observed is only due to the change in density rather than compositional changes or imaging artefacts. Some artefacts, such as beam hardening can be corrected for (see Quantifying 3D images section), or avoided altogether by using a monochromatic beam, such as found on many synchrotron tomography beam lines.…”
Section: Density Measurementsmentioning
confidence: 99%
“…The atomic number of aluminium and the effective atomic number of cortical bone are similar; therefore, conclusions may be drawn on the effect of beam hardening correction on aluminium from its effect on cortical bone and vice versa. 18 Owing to the fact that our phantom is larger in diameter and thickness than the phantom used by Meganck et al, 7 the cupping effect should initially be worse in our 3.8 cm cylindrical aluminium phantom and therefore more difficult to eliminate. Meganck et al 7 used a phantom of 11.811 mm in diameter and demonstrated that the cupping effect due to beam hardening increases as phantom thickness increases.…”
Section: Discussionmentioning
confidence: 93%
“…6 As a result, beam hardening and scatter produce a common artefact known as the cupping effect artefact. [6][7][8][9][10][11][12][13][14] McDavid et al 15 and Brooks and Di Chiro 16 demonstrated that the cupping effect is caused by beam hardening by reconstructing a uniform object with ideal projections and observing the absence of the cupping effect. The cupping effect caused by scatter occurs because of the scatter flux, resulting in an underestimation of the linear attenuation coefficient.…”
Section: Introductionmentioning
confidence: 99%